2003
DOI: 10.1046/j.1365-2222.2003.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Butterbur, a herbal remedy, attenuates adenosine monophosphate induced nasal responsiveness in seasonal allergic rhinitis

Abstract: BB exhibited protection against AMP-induced nasal responsiveness during the grass pollen season in sensitized patients. This is turn may explain its potential clinical efficacy in patients with SAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 15 publications
3
23
0
Order By: Relevance
“…Adult studies showed butterbur proved efficacious compared with placebo in sustaining nasal inspiratory flow while being challenged with a potent nasal congestant, adenosine monophosphate, 93 and when compared with fexofenadine, it provided equally significant effective relief from intermittent allergic rhinitis both by subjective patient ratings and by the physician's global assessment. 94 Urtica dioica is a plant whose leaf, flower, seed, and root each contain different chemical constituents, including histamine, thus the common name stinging nettle.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Adult studies showed butterbur proved efficacious compared with placebo in sustaining nasal inspiratory flow while being challenged with a potent nasal congestant, adenosine monophosphate, 93 and when compared with fexofenadine, it provided equally significant effective relief from intermittent allergic rhinitis both by subjective patient ratings and by the physician's global assessment. 94 Urtica dioica is a plant whose leaf, flower, seed, and root each contain different chemical constituents, including histamine, thus the common name stinging nettle.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…The pyrrolizidine alkaloids of the plant are toxic, thus the reliable removal of these compounds is essential for therapeutic use of extracts. Butterbur has been shown to inhibit the biosynthesis of leukotrienes associated with spasmolytic activity and type-I hypersensitivity (Brune et al, 1993;Bickel et al, 1994;Thomet et al, 2001;Meier and Meier-Liebi, 1994;Schapowal et al, 2004), and has been evaluated to treat asthma and particularly allergic rhinitis (Schapowal et al, 2002(Schapowal et al, , 2004Lee et al, 2003;Jackson et al, 2004aJackson et al, , 2004b.…”
mentioning
confidence: 99%
“…The efficacy of butterbur in persistent allergic rhinitis has yet to be determined. In a small clinical study of twenty patients with grass-pollen-sensitized allergic rhinitis, butterbur was effective at reducing adenosine monophosphate-induced nasal responsiveness during the grass pollen season [59].…”
Section: Leukotriene Inhibitorsmentioning
confidence: 99%